Exploring the impact of airport physical environment on passenger emotion and travel intention - Roslan, Astil Harli; Nasrul, Nasrul; Zaid, Sudirman; Yusuf, Hayat (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore the impact of various dimensions of the physical environment at airports, such as facility functionality, aesthetics, layout accessibility, and cleanliness, on passenger emotions and their travel intentions. Design/Methodology/Approach: The study was conducted at Haluoleo Airport in Kendari, Indonesia, involving 144 passengers who had used airline services more than twice. The survey was conducted between March and May 2024 with approval from airport authorities. The analysis was performed using Structural Equation Modeling (SEM) and AMOS software. The findings show that the physical environment at the airport significantly affects passenger emotions, which, in turn, impacts their travel intentions. This research highlights the importance of improvements in facility functionality, aesthetics, accessibility, and cleanliness to enhance the passenger experience, ultimately improving satisfaction and loyalty to the airport. Practical implications of this study emphasize the importance of airport management in maintaining and enhancing these factors to create a more enjoyable experience for passengers, which will positively impact their satisfaction and loyalty.